FROM NEED TO INNOVATION: DEVELOPING ENGLISH READING INSTRUCTIONAL MATERIAL FOR ISLAMIC EDUCATION DEPARTMENT - Syarif Amin; Maulina Maulina; Geminastiti Sakkir (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study employed a descriptive research method with a mixed-methods approach to investigate the university students’ need in learning English reading at a private university in Southeast Sulawesi province, Indonesia. A descriptive design was used to analyze students’ needs in learning reading—particularly in relation to Islamic content—without manipulating variables. The research design followed a Needs Analysis framework in English for Specific Purposes (ESP), combining questionnaires for quantitative data and interviews for qualitative insights. The findings reveal that students are dominantly motivated by instrumental goals, with 87.75% aiming for better career opportunities, and high percentages driven by examination success (87%) and academic achievement (85%). Reading has been widely identified as a fundamental skill that plays a pivotal role in fostering vocabulary acquisition and enhancing academic literacy, particularly within the domain of Islamic studies. Students also expressed a preference for bilingual instruction, balancing Indonesian and English, to support comprehension and gradual exposure to authentic input. Overall, the study concludes that students’ motivations are multifaceted, encompassing career, academic, and disciplinary needs. These results underscore the importance of designing ESP-based English programs that integrate workplace relevance, academic literacy, and Islamic content within a flexible bilingual pedagogy.